2009
DOI: 10.1179/174328408x353723
|View full text |Cite
|
Sign up to set email alerts
|

On measurement of retained austenite in multiphase TRIP steels — results of blind round robin test involving six different techniques

Abstract: International audienceThe present paper reports the results of a blind round robin test dedicated to the measurement of the retained austenite content of different TRIP assisted multiphase steels. Various surface and volume techniques, i.e. light microscopy, X-ray diffraction, electron backscattered diffraction (EBSD), magnetic saturation, thermal diffusivity and laser ultrasonics, were used by different partners. The compiled results show a quite large variability of the estimated retained austenite content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 18 publications
2
48
0
Order By: Relevance
“…Hence, the characterization of the retained austenite is very important and many studies have been performed so far. [13][14][15][16][17] In most of such works, a specimen was interruptedly quenched during material processing in order to freeze its microstructure at a certain elevated temperature. It is, however, difficult to freeze high temperature microstructure completely and hence not easy to track microstructural evolution continuously at the same observation position of a specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the characterization of the retained austenite is very important and many studies have been performed so far. [13][14][15][16][17] In most of such works, a specimen was interruptedly quenched during material processing in order to freeze its microstructure at a certain elevated temperature. It is, however, difficult to freeze high temperature microstructure completely and hence not easy to track microstructural evolution continuously at the same observation position of a specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Although these problems can be minimized by optimizing the measurement conditions and surface preparation, one should always be careful with these issues. A similar problem has been pointed out in the case of the determination of meta-stable residual austenite fraction in bainitic/martensitic steels [17].…”
Section: Texturementioning
confidence: 90%
“…In comparison to the TEM study conducted by Lee et al [12,15], the EBSD method is able to show the evolution of different phases in a more quantitative manner. Although different characterization techniques of optical microscopy, magnetic measurements, thermal diffusivity, laser ultrasonics, X-ray diffraction (XRD) and EBSD may be used for the phase analysis, it has been shown that there is a quite large variability of the estimated phase content, particularly for the well-established techniques such as XRD and magnetization [21,22]. The EBSD technique is able to successfully determine the volume fraction of the microstructural constituents and also to measure the local orientations and orientation gradients within individual grains of the composing constituents.…”
Section: Introductionmentioning
confidence: 99%